Smart win–win waste management: superhydrophobic filter using valorized cellulose acetate from discarded cigarette butts for cleaning up marine oil spill at Hurghada Red Sea shore in Egypt - Nabwey, Hossam A.; Abdelkreem, Maha; Tony, Maha A.; Al Hoseny, Noha F. (Frontiers in Marine Science, 2024)
The essential target of academics and industrial sectors is innovating an industrial ecology approach.Worldwide cigarette butts are the most predominant form of litter that spread into the ecosystem and inland.At the meantime, oil is spilled into the marine life due to various activities and transportation. The result is a complex oil-water composition in a high concentration that cause a severe hazardous to the environment and aquatic life. According to this regard, the current investigation is dealing with attaining of hydrophobic cellulose acetate from cigarette butts (CBs) for being a filter media. The filter is applied for marine oil spill separation as a win-win industrial ecology technique. Initially, the separated CBs residuals are prepared by successive washing facility then the attained cellulose acetate fibers that are characterized by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). Further, the new filter-based CBs are used in the separation/adsorption of marine oil wastewater spill. Then a group of experiments were conducted and the results showed that the cleanup efficiency could be reached to 99% in terms of COD (chemical oxygen demand). Also, the products were recovered by washing with hot water for further use, which showed a high removal activity reached to 95% after successive use. In comparison to the commercial oil sorption materials, the results are promising since the RP-C18 cartridge revealed a maximum oil removal of 90%. Such preliminarily data of a cellulose acetate filter scheme is a good indicator in developing an oil spill facility being a suitable candidate for controlling oil wastewater effluent streams.